2
$\begingroup$

In the case of free, undamped vibrations,the differential equation is $mu''+ku=0$ and solution to this differential equation is

\begin{align} \tag{1} u(t)=c_1\cos{(\omega_0 t)}+c_2\sin{(\omega_0 t)} \end{align}

Now this has been written by the author in the following form,

\begin{align} \tag{2} u(t)=R\cos{(\omega_0 t-\delta)} \end{align}

where he says R is the amplitude of displacement $u(t)$ and $\delta$ is the phase shift or phase angle of displacement $u(t)$

Now why did he assume that both the equations $(1)$ and $(2)$ are equivalent and on what ground?

$\endgroup$
4
$\begingroup$

One can use $$c_1=R\cos\delta\\c_2=R\sin\delta$$ or one can go the other way around $$R=\sqrt{c_1^2+c_2^2}\\ \delta=\arctan{c_2/c_1}$$ Then: $$c_1\cos\omega_0 t+c_2\sin\omega_0 t=R(\cos\omega_0t\cos\delta+\sin\omega_0t\sin\delta)=R\cos(\omega_0t-\delta)$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ How the $c_1$ and $c_2$ is calculated? $\endgroup$ – Dhamnekar Winod Oct 20 '18 at 4:34
  • $\begingroup$ You need to have some initial conditions (like position $u(t=0)$ and speed $u'(t=0)$) $\endgroup$ – Andrei Oct 20 '18 at 4:38
  • $\begingroup$ suppose $u(t)=-\frac12 \cos{(6t)}+\frac16 \sin{(6t)}$ and in another form $u(t)=0.52705 \cos{(6t-2.81984)}$ where $R=0.52705$ and $\delta=2.81984$ Now i want the displacement at 5 seconds, so both the equations must be equal. But it is not so. What is wrong? $\endgroup$ – Dhamnekar Winod Oct 20 '18 at 5:16
  • 1
    $\begingroup$ I get for both of them $-0.2418$. Make sure you use radians $\endgroup$ – Andrei Oct 20 '18 at 5:35
  • $\begingroup$ If i use $u(t)=R \sin{(\omega_0t+ \delta)} $ shall i get the correct answer? $\endgroup$ – Dhamnekar Winod Oct 20 '18 at 16:37
3
$\begingroup$

If $c_1=c_2=0$ you may take any $\delta$ and $R=0$. Otherwise put $R:=\sqrt{c_1^2+c_2^2}$ and observe that $d_1^2+d_2^2=1$ where $d_i:=\frac{c_i}{R}$. Thus there ist some $\delta$ auch that $d_1=\cos\delta$ and $d_2=\sin\delta$. Finally note that $\cos\delta \cos(\omega_0 t)+\sin\delta \sin(\omega_0 t)=\cos(\omega_0 t-\delta)$ by the subtraction formula of $\cos$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.